The Application of Mixed Method in Developing a Cyber Terrorism Framework - Ahmad, Rabiah; Yunos, Zahari (2012)
Mixed method research has becoming an increasingly popular approach in the discipline of sociology, psychology, education, health science and social science. The purpose of this paper is to describe the application of mixed method in developing a cyber terrorism framework. This project has two primary goals: firstly is to discover the theory and then develop a conceptual framework that describes the phenomena, and secondly is to verify the conceptual framework that describes the phenomena. In order to achieve conclusive findings of the study, a mixed method research is recommended: qualitative data and quantitative data are collected and analyzed respectively in a separate phase. The mixed method approach improves the rigor and explanation of the research results, thus bring conclusive findings to the study outcome. By utilizing qualitative and quantitative techniques within the same study, we are able to incorporate the strength of both methodologies and fit together the insights into a workable solution.